Software defined radio based radar demonstrator Part 2 - Ren, Rui (2011)
Software defined radio (SDR) has emerged as a priority theme of research since it will substitute for conventional implementation on radar system. This project investigates the knowledge of Software Defined Radio and successfully built up a piecewise SDR chirp transmitter using MATLAB on the platform of ICS-564. The ICS-564 is a single width PMC module that includes four 14-bit 200 MHz Digital-to-Analog Converters. In this project, a properly programmed MATLAB Graphical User Interface is developed to control the ICS-564 board to generate desired IF chirp analog waveforms. The output waveform, i.e. the transmission chirp signal is designed as piecewise linear frequency to meet various user requirements and application demands. MATLAB Simulations shows that the proposed transmission scheme works well to fulfill the design requirements and is applicable in practical applications. Four sets of tests to examine the system performance are conducted in the final stage of the project.